RETRACTED: Pengaruh Senam SKJ 2008 Terhadap Kebugaran Jasmani Siswi Sekolah Dasar Negeri 20 Alang Laweh Padang Selatan Kota Padang - Lusi Oktaviani; Arfon Meirony (UIR Press, 2017)
This article has been withdrawn at the request of the Chief Editor. The reason for the withdrawal is that this article also published in the Jornal of Education Research and Evaluation. link: https://ejournal.undiksha.ac.id/index.php/JERE/article/view/11694. The condition for submitting a work for publication is that the author explicitly states that all of his works are original and have not appeared in publications elsewhere. We apologize to journal readers that this was not detected during the delivery process.